Quotations and (Lost) Commentaries in Advaita Vedānta: Some Philological Notes on Bhartṛprapañca’s “Fragments” - Andrijanić, Ivan (2014)
The oldest preserved commentary on the Br̥hadāraṇyaka-Upaniṣad was composed by Śaṅkara. Sureśvara composed a sub-commentary on this commentary, while Ānandagiri composed commentaries both on Śaṅkara’s commentary and on Sureśvara’s sub- commentary. All these four books contain a number of passages from earlier works which are not preserved. Sureśvara and Ānandagiri attributed some of these passages to a commentator named Bhartṛprapañca. The aim of this article is to present a philological method which will establish which of the passages might be paraphrases and which might be quotations from Bhartṛprapañca’s lost commentary composed in the scope of the bhedābheda theory. This article will argue that Śaṅkara paraphrases Bhartṛprapañca’s text, while Ānandagiri quotes most probably Bhartṛprapañca’s text literally. This text was metrically adjusted by Sureśvara who paraphrases Bhartṛprapañca by shortening and adjusting the original text (preserved in Ānandagiri’s accounts) in order to fit into the pattern of the śloka meter. If this is true, it is possible to establish a methodology which may help us to reconstruct portions of the oldest known commentary on the Br̥hadāraṇyaka-Upaniṣad.
Projekt MZOS
ENG